เทคนิคการเรียนการสอนสัทศาสตร์เบื้องต้นสำหรับครูภาษาอังกฤษ - โชติชัย, บรรจบ (วารสารศรีล้านช้างปริทรรศน์, 2020)
ในการสอนภาษาอังกฤษเพื่อให้ได้ประสิทธิผลด้านการสื่อสาร ครูผู้สอนภาษาอังกฤษจำเป็นต้องเริ่มต้นด้วยการสอนให้นักเรียนสามารถออกเสียงได้อย่างถูกต้องหรือใกล้เคียงกับเจ้าของภาษา การฝึกฟังและฝึกออกเสียงจึงเป็นทักษะสำคัญที่ครูผู้สอนต้องให้ความสนใจอย่างมาก การสอนการออกเสียงตามหลักสัทศาสตร์ถือว่าเป็นแนวทางที่ถูกต้องในการเรียนรู้เพื่อฝึกฟังและฝึกออกเสียงภาษาอังกฤษเพราะผู้เรียนจะได้เข้าใจว่าเสียงต่าง ๆ ที่ได้ยินนั้นมีที่มาอย่างไร เกี่ยวข้องหรือสัมพันธ์กันอย่างไร การเรียนรู้การเกิดเสียง ตำแหน่ง และลักษณะของเสียงที่เกิด รวมไปถึงปัญหาของการออกเสียง จะช่วยให้การเรียนรู้เพื่อการฝึกฟังและฝึกออกเสียงบรรลุวัตถุประสงค์ของการเรียนภาษาอังกฤษเพื่อการสื่อสารมากที่สุด             In English teaching for higher communicative proficiency, how to teach the students able to pronounce English properly or like any native speaker was an initial start for all English teachers. Training the students to listen to and pronounce proper English was an important skill for English teachers to pay attention to. In addition, the phonetic pronunciation was regarded a proper way for English listening and pronunciation because learners could understand how those sounds were derived and related to each other. Knowledge on sound production, sound places and manners, and pronunciation problems would assist learning of English listening and pronunciation to attain the objectives of communicative English learning.